2023
DOI: 10.1111/jade.12454
|View full text |Cite
|
Sign up to set email alerts
|

Is Creativity Masculine? Visual Arts College Students’ Perceptions of the Gender Stereotyping of Creativity and Its Influence on Creative Self‐Efficacy

Abstract: This study investigated visual arts college students’ perceptions of the gender stereotyping of creativity and the influence of this stereotyping on creative self‐efficacy. The sample consisted of 1198 Chinese visual arts college students. The results showed that (a) both male and female students identified stereotypically masculine traits as more important to creativity than stereotypically feminine traits are, (b) male students demonstrated higher creative self‐efficacy than their female counterparts did, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Stoltzfus et al (2011) found that androgynous individuals had significantly higher cognitive flexibility scores compared to those whose gender roles were described as female or undifferentiated. Luo et al (2023) concluded that male students exhibited higher creative self-efficacy perceptions than female students. Males are generally considered to have higher creative self-efficacy and creativity due to biases associated with gender stereotypes (Charyton et al, 2008;Proudfoot et al, 2015;Luksyte et al, 2018;Luo et al, 2023).…”
Section: Innovative Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…Stoltzfus et al (2011) found that androgynous individuals had significantly higher cognitive flexibility scores compared to those whose gender roles were described as female or undifferentiated. Luo et al (2023) concluded that male students exhibited higher creative self-efficacy perceptions than female students. Males are generally considered to have higher creative self-efficacy and creativity due to biases associated with gender stereotypes (Charyton et al, 2008;Proudfoot et al, 2015;Luksyte et al, 2018;Luo et al, 2023).…”
Section: Innovative Achievementmentioning
confidence: 99%
“…Luo et al (2023) concluded that male students exhibited higher creative self-efficacy perceptions than female students. Males are generally considered to have higher creative self-efficacy and creativity due to biases associated with gender stereotypes (Charyton et al, 2008;Proudfoot et al, 2015;Luksyte et al, 2018;Luo et al, 2023). Due to the traditional gender division of labor, females have adaptive creativity, while males have both innovative and adaptive creativity (Stoltzfus et al, 2011).…”
Section: Innovative Achievementmentioning
confidence: 99%